2014
DOI: 10.1159/000437350
|View full text |Cite
|
Sign up to set email alerts
|

Remyelination after Lysophosphatidyl Choline-Induced Demyelination Is Stimulated by Bone Marrow Stromal Cell-Derived Oligoprogenitor Cell Transplantation

Abstract: Bone marrow stromal cells (BMSCs) are a desirable cell source that may be useful for the treatment of neurodegenerative diseases given their capacity to differentiate into various types of cells. The current study aimed to investigate whether oligoprogenitor cell (OPC)-derived BMSCs have therapeutic benefits in an animal model of local demyelination. BMSCs were transdifferentiated into OPCs using a defined culture medium supplemented with a combination of inducers. The differentiation capacity of the BMSCs was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 31 publications
(30 reference statements)
1
16
0
Order By: Relevance
“…Therefore, our study showed that adding CSF in culture as inducer medium provided suitable nutrient microenvironment for survival, proliferation and differentiation of hDPSCs. Overall, results of the present study suggest that the cytotoxicity of the CSF will affect the survival rate of the cells in a dose-dependent pattern [202122]. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, our study showed that adding CSF in culture as inducer medium provided suitable nutrient microenvironment for survival, proliferation and differentiation of hDPSCs. Overall, results of the present study suggest that the cytotoxicity of the CSF will affect the survival rate of the cells in a dose-dependent pattern [202122]. …”
Section: Discussionmentioning
confidence: 99%
“…It can be noted that BMP4 activate the protein chain called extracellular signal-regulated kinases (ERK). These proteins (ERK) act as signal transmitter from cell surface receptors to the cell nucleus and nucleic acid, leadings to the expression of different enzymes and proteins and providing the neural differentiation of neural progenitor cells [2122232427282930]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…OPC can be generated from fibroblasts by direct reprogramming[ 25 26 27 ] by ectopic expression of defined transcriptional factors. Induced OPC (iOPC) can expand in vitro and differentiate into mature OL ensheathing host axons and generating compact myelin.…”
Section: Differentiation Into Oligodendrocyte Precursor Cells From Stmentioning
confidence: 99%